2018
DOI: 10.2147/idr.s175584
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance phenotype and clinical molecular epidemiology of carbapenem-resistant <em>Klebsiella pneumoniae</em> among pediatric patients in Shanghai

Abstract: BackgroundCarbapenem-resistant Klebsiella pneumoniae (CRKP) has caused wide global disseminations and serious clinical outcomes in pediatric patients, and the purpose of this study was to analyze drug resistance, molecular epidemiology, and clinical characteristics of CRKP from children in Shanghai, China.MethodsA retrospective study was conducted from January 2016 to December 2017, and a total of 170 CRKP isolates were collected. Antimicrobial susceptibility was determined by the broth microdilution method. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 28 publications
4
34
3
1
Order By: Relevance
“…These findings described the different patterns of carbapenemases among CRE strains from adults and children. In contrast to the previous finding that NDM-1 was the most common carbapenemase among children patients, we have found that NDM-5-producers (32.9%) were most frequently detected CRE strains from children (Tian et al, 2018;Yin et al, 2018;Zhang et al, 2018). The outbreak of NDM-5-producing ST48 K. pneumoniae was first reported in Shanghai (Tian et al, 2018).…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…These findings described the different patterns of carbapenemases among CRE strains from adults and children. In contrast to the previous finding that NDM-1 was the most common carbapenemase among children patients, we have found that NDM-5-producers (32.9%) were most frequently detected CRE strains from children (Tian et al, 2018;Yin et al, 2018;Zhang et al, 2018). The outbreak of NDM-5-producing ST48 K. pneumoniae was first reported in Shanghai (Tian et al, 2018).…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast to the previous finding that NDM-1 was the most common carbapenemase among children patients, we have found that NDM-5-producers (32.9%) were most frequently detected CRE strains from children (Tian et al, 2018;Yin et al, 2018;Zhang et al, 2018). The outbreak of NDM-5-producing ST48 K. pneumoniae was first reported in Shanghai (Tian et al, 2018). We speculated that outbreak of NDM-5-producers accounted for the spread of NDM-5 among children patients in this study (Tian et al, 2018;Li et al, 2020).…”
Section: Discussioncontrasting
confidence: 84%
“…Galani et al (2019) detected 300 CRKP strains in hospitals across Greece and found KPC-2 (66Á7%), NDM (16Á7 %), VIM (7%) and OXA-48 (4Á0%); 14 strains carried both KPC and VIM (4Á7%), two strains carried both NDM and OXA (0Á7%) and one strain carried both KPC and OXA (0Á3%) resistance genes. Tian et al (2018) retrospectively analysed the drug-resistant phenotypes and clinical molecular epidemiology of 170 CRKP strains in Shanghai from January 2016 to December 2017 and found that the most abundant gene was bla OXA-232 (42Á35%), followed by bla NDM-1 (20Á59%), bla KPC-2 (17Á65%), bla NDM-5 (16Á47%) and bla IMP-4 (1Á18%). Furthermore, they found that the genes present were related to different ages and epidemic strains in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (Bruker Daltonics GmBH, Bremen, Germany) was used for bacterial identification, and disc diffusion assays (for imipenem and meropenem) were used to identify carbapenem resistance. Common carbapenemase genes (bla KPC , bla NDM , bla IMP , bla OXA-48 , bla VIM , bla AIM , bla GIM , and bla SIM ) were amplified for all strains using primers from the previous study, and the positive products were sequenced (2). Twenty-two bla NDM-5 -positive strains were finally selected for further study.…”
Section: Methodsmentioning
confidence: 99%
“…KEYWORDS NDM-5, Enterobacteriaceae, ST48, IncX3-type plasmid, carbapenemase, children, Enterobacterales C arbapenemase-producing Enterobacteriaceae (CRE) have become a serious challenge to clinical therapy owing to the rapid worldwide dissemination of multidrug resistance (MDR) (1). New Delhi metallo-␤-lactamase (NDM) is the main carbapenemase detected in children (2), which is capable of hydrolyzing almost all ␤-lactams and has the potential to cause a global health crisis. Since the first report of NDM-1, 21 variants of NDM enzymes (NDM-1 to NDM-21) have been identified worldwide (3).…”
mentioning
confidence: 99%